‘One cannot legislate kindness’: ambiguities in European legal instruments on non-custodial sanctions - Van Zyl Smit, Dirk; Snacken, Sonja; Hayes, David J. (Sage, 2014)
Non-custodial sanctions, particularly those that are implemented in the community, have different historical roots in common and civil law jurisdictions. Nevertheless, various European instruments seek to shape the imposition and implementation of such sanctions uniformly across the continent. These instruments reflect an apparent consensus about penal values, culminating in 1992 with the adoption of the European Rules on Community Sanctions and Measures and of the Recommendation on Consistency in Sentencing. In spite of the apparent pan-European consensus, some tensions remained as a result of underlying doctrinal differences and of the compromises that were required to accommodate them. In the 21st century further European initiatives have sought to go beyond the 1992 instruments and focus on ‘what works’ and on the development of probation services. In the process, the central objective of penal reductionism, so important in 1992, has become somewhat marginalised. This shortcoming can be addressed by reconsidering the approaches that had been rejected in the earlier search for consensus and by developing a more comprehensive understanding of the human rights safeguards to which all penal sanctions should be subject.